New District Creation in Uganda and Local Actors: Passive Recipients or Active Pursuers? - Tabaro, Robert; Katusiimeh, Mesharch; Molenaers, Nadia (Journal of public administration and governance, 2018)
From the 1990s, Uganda embarked on a process of subdividing administrative units (districts) as part of the decentralization programme supposedly to bring services closer to the people. Li terature has, however, shown that in most of the cases the process is used as a strategy by the incumbent president Museveni for his political survival. As such, new district creation is seen as a process driven by central political elites. The role of lo cal policy entrepreneurs (actors) has thus been given limited attention. Basing on thirty five elite interviews and document review, we established that local policy entrepreneurs do matter in policy change processes and can at times challenge the position of central political elites. Focusing on the new district of Sheema in western Uganda (split from ‘mother’ district of Bushenyi in 2010), we found out that president Museveni who initially ‘opposed’ the idea of a new district had to finally give in to peo ples’ demands. This was because local policy entrepreneurs in Sheema were determined, eager, highly motivated and smart in strategizing and forming alliances in the pursuit of their goals. But also because the president feared vote loss as demands gained m omentum towards the 2011 general elections.
Keywords: New district creation; Decentralization; Local actors; Policy entrepreneurs